Effectiveness of a Patient Blood Management Data System in Monitoring Blood use in Western Australia. Issue 2 (March 2013) - Mukhtar, S. A.; Leahy, M. F.; Trentino, K.; Koay, A.; Semmens, J. B.; Tovey, J.; Jewlachow, V.; Farmer, S. L.; Hofmann, A.; Roberts, H. A.; Towler, S. C.
The aim of this paper is to describe a linked patient blood management (PBM) data system and to demonstrate its usefulness by presenting the blood usage data obtained. Our existing datasets already collected much of the required information in relation to PBM. However, these datasets were not linked. A patient identifier was used to link the Patient Administration System with the Laboratory Information System. Data linkage was achieved by linking the Laboratory Information System with the Patient Administration System records where blood transfusion or laboratory result date/time fell between admission and discharge date/time. The two datasets were then consolidated into the PBM data system. Blood usage data obtained from the system showed that between August 2008 and July 2009 there were 59, 627 patient completed separations in the pilot hospital. Of the total transfused units, 62% were red blood cells (RBC), followed by fresh frozen plasma (22%), cryoprecipitate (9%) and platelets (8%). Around 50% of RBC transfusions were administered to patients >70 years of age. General medicine represented 21% of RBC usage, followed by haematology (19%), orthopaedics (17%) and general surgery (16%). Patients with 100 g/1 pre-transfusion haemoglobin received 9% of RBC transfusions and patients with 71–100 g/1 pre-transfusion haemoglobin received 73% of RBC transfusions. The post-transfusion haemoglobin in RBC transfusions exceeded 100 g/1 in 33% of patients. Databases were successfully linked to produce a powerful tool to monitor blood utilisation and transfusion practices within a pilot PBM program. This will facilitate effective targeting of PBM strategies and ongoing monitoring of their impact.